Modeling Tree Growth Taking into Account Carbon Source and Sink Limitations - Hayat, Amaury; Hacket-Pain, Andrew J.; Pretzsch, Hans; Rademacher, Tim T.; Friend, Andrew D. (Frontiers in Plant Science, 2017)
Increasing CO2 concentrations are strongly controlled by the behavior of established forests, which are believed to be a major current sink of atmospheric CO2. There are many models which predict forest responses to environmental changes but they are almost exclusively carbon source (i.e., photosynthesis) driven. Here we present a model for an individual tree that takes into account the intrinsic limits of meristems and cellular growth rates, as well as control mechanisms within the tree that influence its diameter and height growth over time. This new framework is built on process-based understanding combined with differential equations solved by numerical method. Our aim is to construct a model framework of tree growth for replacing current formulations in Dynamic Global Vegetation Models, and so address the issue of the terrestrial carbon sink. Our approach was successfully tested for stands of beech trees in two different sites representing part of a long-term forest yield experiment in Germany. This model provides new insights into tree growth and limits to tree height, and addresses limitations of previous models with respect to sink-limited growth.